Efektivitas Aplikasi AToluCare Dengan Pendekatan Budaya Batak Dalam Meningkatkan Pengetahuan Sikap dan Dukungan Pencegahan Anemia Pada Ibu Hamil: Effectiveness of AToluCare Application with Batak Cultural Approach in Enhancing Knowledge, Attitudes, and Support for Anemia Prevention Among Pregnant Women - Purba, Edy Marjuang; Sandy, Yatty Destani; Naibaho, Zanrison (Universitas Airlangga, 2026)
Background: The prevalence of anemia among pregnant women in Indonesia remains high, with 27.7% reported in the 2023 Indonesia Health Survey. This condition is influenced by low levels of knowledge and awareness, inadequate attitudes toward prevention, and limited family support. Dalihan Na Tolu, a Batak cultural philosophy that emphasises the roles of hula-hula (providing guidance and advice), dongan tubu (ensuring vigilance and mutual supervision), and boru (offering practical and tangible support), has been incorporated into the AToluCare application as a culturally grounded educational and supportive innovation. Objectives: : To analyze the effect of the AToluCare application with a Batak cultural approach in improving knowledge, attitudes, and Dalihan Na Tolu support for anemia prevention among pregnant women. Methods: A quasi-experimental study with a pre-test and post-test design was conducted in Humbang Hasundutan District. Ninety pregnant women were selected through multistage sampling. The intervention involved using the AToluCare application for one month. Valid and reliable questionnaires were used to measure knowledge, attitudes, and Dalihan Na Tolu support. Data were analyzed using the Wilcoxon signed-rank test. Results: Most participants were aged 20–35 years (58.89%), had higher education (75.56%), were employed (70.00%), had parity ≤2 (61.11%), and attended antenatal care regularly (64.44%). Significant improvements were observed in mean scores of knowledge (11.28±2.76 to 16.10±2.40; p-value=0.001), attitudes (39.97±6.86 to 43.22±4.19; p-value=0.008), and Dalihan Na Tolu support (34.12±6.23 to 40.47±5.45; p-value=0.001). Conclusions:The AToluCare application, which incorporates a Batak cultural approach, has been shown to effectively improve knowledge, attitudes, and family support related to anemia prevention among pregnant women. Integrating this application into existing healthcare programs may offer a sustainable, culturally grounded strategy for reducing anemia during pregnancy.